PROCEDURE FOR INTRAVENOUS PYELOGRAPHY EXAMINATION IN POST-URETERORENOSCOPY PYELOLITHIASIS PATIENTS AT PANEMBAHAN SENOPATI BANTUL HOSPITAL RADIOLOGY - Alifta Aulia Fathin; Retno Wati; Ari Anggraeni (Journal of Indonesian Anesthesiology Nursing, 2024)
Background: Intravenous Pyelography (IVP) is a radiographic technique used to visualize the urinary system by injecting contrast media intravenously. At Panembahan Senopati Bantul Hospital, IVP is utilized post-ureterorenoscopy for patients with clinical pyelolithiasis to detect residual stones. The procedure requires specific pre-exam preparations, and AP supine imaging is conducted at planning stages and at 5, 15, and 30 minutes post-injection to observe contrast flow. This study aims to examine the IVP procedure and its significance in postoperative care, providing insights into the role of IVP in managing stone removal and obstructions. Methods: This qualitative, descriptive research was conducted from August 2023 to August 2024 at Panembahan Senopati Hospital, Bantul. The study focused on IVP procedures for post-ureterorenoscopy pyelolithiasis patients, involving three radiographers, one radiologist, and one referring doctor. Data collection included observation, interviews, documentation, and literature, with analysis through reduction, presentation, and conclusion techniques to understand the procedure’s purpose and role in patient management. Results: The study found that the IVP procedure for post-ureterorenoscopy pyelolithiasis requires special preparations, including x-ray equipment, iohexol contrast media, and an intravenous cannula. Iohexol is administered via drip infusion, with AP supine images taken at baseline, and 5, 15, and 30 minutes post-injection. This sequence helps assess any residual stones. Conclusion: A wing needle is recommended for controlled contrast injection, allowing the procedure to be halted quickly if allergic reactions occur. This setup provides clearer assessment and enhances patient safety during imaging. Recommendation and implication of the study must be clear. It should not contain any references or displayed equations.